"One Health" and global health governance: Design and implementation at the international, European, and German levels - Michael Bayerlein; Pedro A. Villarreal (Stiftung Wissenschaft und Politik (SWP), 2023)
The "One Health" approach has found its way into political processes at various levels. The reason for this is the increased occurrence of zoonoses, i.e. infectious diseases that can be reciprocally transmitted between animals and humans. One Health is located at the intersection of human, animal, and ecosystem health on the one hand and calls for trans-sectoral solutions on the other. Numerous substantive issues beleaguer the practical design of the One Health approach as well as its implementation by the World Health Organization (WHO), regional institutions, and states. One Health is currently being addressed in three contexts in particular: in the negotiations on the pandemic treaty, in the EU's Global Health Strategy, and in the German government's strategy on global health.
Keywords: 320; One Health; Global Health Governance; EU Global Health Strategy; Pandemic Treaty; zoonoses; Antimicrobial resistance; AMR; International Health Regulations; IHR; Global Early Warning System; GLEWS+